2018
DOI: 10.2196/resprot.7655
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Participant Validity in a Small Internet Health Survey (The Restore Study): Protocol and Recommendations for Survey Response Validation

Abstract: BackgroundWhile deduplication and cross-validation protocols have been recommended for large Web-based studies, protocols for survey response validation of smaller studies have not been published.ObjectiveThis paper reports the challenges of survey validation inherent in a small Web-based health survey research.MethodsThe subject population was North American, gay and bisexual, prostate cancer survivors, who represent an under-researched, hidden, difficult-to-recruit, minority-within-a-minority population. In … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 24 publications
(27 reference statements)
1
53
0
Order By: Relevance
“…Dewitt et al [ 37 ] states internet-based research as “advantageous to essential” in recruiting niche communities; but that it also brings forth a new validation issue that the researcher will never meet their participants. This can lead to the same participant completing the survey multiple times and ineligible participants completing the survey.…”
Section: Discussionmentioning
confidence: 99%
“…Dewitt et al [ 37 ] states internet-based research as “advantageous to essential” in recruiting niche communities; but that it also brings forth a new validation issue that the researcher will never meet their participants. This can lead to the same participant completing the survey multiple times and ineligible participants completing the survey.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that specific ailments associated with HIV, such as cardiovascular disease, mental illness, or hormonal imbalances, are associated with poor rehabilitation after prostate cancer treatment . In addition, mental and physical comorbidities have been associated with poor HRQOL in people living with HIV . However, it is unclear why these comorbidities did not also lead to an association between HIV and overall HRQOL.…”
Section: Discussionmentioning
confidence: 99%
“…Fraudulent responses (n = 289) were excluded from analysis. Procedures to identify duplicitous participants are described elsewhere …”
Section: Methodsmentioning
confidence: 99%
“…In addition, the survey did not use a tool like a Completely Automated Public Turing Test to tell Computers and Humans Apart, which could have reduced fraud by requiring respondents to verify that they were not robots [30]. However, previous research has demonstrated that Completely Automated Public Turing Test to tell Computers and Humans Apart tool verification is not failproof and can be passed despite an entry being invalid or fraud [21].…”
Section: Methodsmentioning
confidence: 99%
“…The confidentiality and anonymity of Web-based research make it difficult to prevent such entries, posing a threat to data integrity if appropriate data quality protocols are not in place [4,7,13-15,17-20]. Bots and smart software that have the capability to produce human-like data with unique Internet Protocol (IP) addresses can also lead to invalid or fraudulent data [21]. Computer program (ie, bots) and human fraud must both, therefore, be considered in fraud identification strategies.…”
Section: Introductionmentioning
confidence: 99%